2014
DOI: 10.1186/1472-6750-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design approach in recombinant protein expression: determining medium composition and induction conditions for expression of pneumolysin from Streptococcus pneumoniae in Escherichia coliand preliminary purification process

Abstract: BackgroundStreptococcus pneumoniae (S. pneumoniae) causes several serious diseases including pneumonia, septicemia and meningitis. The World Health Organization estimates that streptococcal pneumonia is the cause of approximately 1.9 million deaths of children under five years of age each year. The large number of serotypes underlying the disease spectrum, which would be reflected in the high production cost of a commercial vaccine effective to protect against all of them and the higher level of amino acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 38 publications
3
48
0
3
Order By: Relevance
“…CHEF1-based expression vector containing the 4.1 kb upstream and 4.2 kb downstream flanking regions of the CHO-EF1 gene was used to express recombinant proteins in mammalian cells [9]. Although these flanking sequences improve expression considerably, their incorporation into the promoter region leads to an increase in the vector size which could cause difficulties in cells transfection and genomic stability [27]. Formerly, the efficiency of CHEF promoter region excluding flanking regions was examined for expression of enhanced green fluorescent protein, EGFP, in stem cells and CHO-K1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…CHEF1-based expression vector containing the 4.1 kb upstream and 4.2 kb downstream flanking regions of the CHO-EF1 gene was used to express recombinant proteins in mammalian cells [9]. Although these flanking sequences improve expression considerably, their incorporation into the promoter region leads to an increase in the vector size which could cause difficulties in cells transfection and genomic stability [27]. Formerly, the efficiency of CHEF promoter region excluding flanking regions was examined for expression of enhanced green fluorescent protein, EGFP, in stem cells and CHO-K1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that immune response can depend on the molecular structure of recombinant HA protein [28]. A previous study has shown that purified rH3 HA forms rosette-shaped subviral particles (SVPs) of approximately 30–50 nm in diameter [29]. However, it is not clear if such SVPs are also formed by rH7 HA and if rH7 HA SVPs are capable of inducing protective immunity in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…However, rHA is also immunogenic and protective in animal models and in humans [61,64]. Immunogenicity of rHA at least in part can be explained by the observed arrangement of rHA into subviral particles, SVP, with up to 30–50 nm in diameter and containing multiple rHA molecules [66]. Thus, it appears that successful recombinant vaccines including L1-based HPV, HBsAg-based HBV, and even rHA-based influenza represent particulate structures such as VLPs or SVP, with oligomeric/particulate structures likely responsible for high immunogenicity of these vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that purified rH3 HA forms rosette-shaped subviral particles (SVPs) of approximately 30–50 nm in diameter [66]. We recently prepared the full-length H7 rHA from A/Anhui/1/2013 (H7N9) using a modified purification conditions for rH7 HA [67].…”
Section: Subunit Rha Vaccinesmentioning
confidence: 99%